The Effect Of Report Text To Student's Writing Quality By Using Instagram Post - Novita, Amelia; Daulay, Sholihatul Hamidah; Ramadhan, Achmad (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2023)
This study aims to determine students' ability to understand how to write a report text using Instagram posts in eighth-grade students at SMPIT AL-FAKHRI SUNGGAL. This research is an experimental research. This study's population was all class VIII students at SMPIT AL-FAKHRI Sunggal. The sample for this study was taken from 30 students in the experimental group (class VIII-A) and 30 students in the control group (class VIII-B). Data collection instruments are in the form of tests and observations. After analyzing the data, the writer gets the highest average value obtained in the experimental class is 2,247. For the control class, the value in the table is around 1,935, so the value received is higher than the table. This means that there is a significant effect of using Instagram posts to write a report text.